2002
DOI: 10.3233/nre-2002-17209
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise intervention improves aerobic capacity and movement initiation in Parkinson's disease patients

Abstract: Parkinson's Disease (PD) is a progressive neurologic disorder, which includes an inability to activate appropriate muscle activity. Very little research has analyzed aerobic exercise for PD patients. The purpose of this study was to investigate the effect of a 16 week aerobic exercise intervention on aerobic capacity and movement initiation (MI) time for PD patients. With 8 PD subjects (Hoehn & Yahr stage 2), 4 completed the exercise intervention. Peak VO2 scores significantly improved (26%) following the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…The clinical importance of movement economy in PD is indirectly supported by several studies demonstrating aerobic exercise benefit for people with PD. 5,[41][42][43][44][45] Building from this study, future work should evaluate mechanisms related to poorer walking economy and the response of walking economy to various interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical importance of movement economy in PD is indirectly supported by several studies demonstrating aerobic exercise benefit for people with PD. 5,[41][42][43][44][45] Building from this study, future work should evaluate mechanisms related to poorer walking economy and the response of walking economy to various interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no known study exists using aerobic exercise, PD, and the BP. Recent support has shown that, in combination with regular PD medication (Bergen et al 2002) and when medication is removed (M€ uller and Muhlack 2010), aerobic exercise not only improves cardiovascular function but also alleviates common symptoms of akinesia and bradykinesia when compared to age-and behavior-matched controls. One interesting venue for exploration is whether aerobic exercise is able to recapture early BP in PD patients.…”
Section: Future Considerationsmentioning
confidence: 99%
“…2005; Farley, 2004;National Parkinson Foundation, 2005;Weiner, Shulman, & Lang, 2001). Studies involving individuals with PD have shown that exercise can be beneficial in improving movement initiation (Bergen et al, 2002), short-step gait (Miyai et al, 2002), flexibility and physical function (Palmer, Mortimer, Webster, Bistevins, & Dickinson, 1986;Schenkman et al, 1998), and quality of life (Baatile, Langbein, Weaver, Maloney, & Jost, 2000;Reuter, Engelhardt, Stecker, & Baas, 1999).…”
mentioning
confidence: 99%